2010
DOI: 10.3109/19396368.2010.519814
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Symptomatic Vasitis: Clinical Correlations in a Rare Condition

Abstract: Vasitis, or inflammation of the vas deferens, is a rare condition. When diagnosed pathologically, it has been linked to vasectomy, prostatectomy, and herniorrhaphy. When diagnosed clinically, relationships with potential causative factors are unclear. We investigated the clinical factors associated with clinically symptomatic vasitis in a retrospective series of patients. From the history, physical examination, and clinical course, we analyzed associated risk factors. Clinical care patterns were also examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Of the eleven subjects, eight had previous surgeries in the neighboring regions, such as herniorrhaphy, prostatectomy, and perianal fistulectomy. The review also proposed other risk factors such as trauma history, concurrent human immunodeficiency virus/herpes simplex virus infections, and smoking habits [10]. Interestingly, our patient had none of the aforementioned risks factors.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Of the eleven subjects, eight had previous surgeries in the neighboring regions, such as herniorrhaphy, prostatectomy, and perianal fistulectomy. The review also proposed other risk factors such as trauma history, concurrent human immunodeficiency virus/herpes simplex virus infections, and smoking habits [10]. Interestingly, our patient had none of the aforementioned risks factors.…”
Section: Discussionmentioning
confidence: 72%
“…Due to the low prevalence nature of acute vasitis, other risk factors have not been credited to this condition. A retrospective review was conducted by Clavijo et al in 2010 where the clinical characteristics of eleven patients were thoroughly evaluated [10]. Of the eleven subjects, eight had previous surgeries in the neighboring regions, such as herniorrhaphy, prostatectomy, and perianal fistulectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews showed this to be predominantly an "adult" disease. 3,4 The more rare form of vasitis, known as infectious vasitis, is considered to be secondary to a local spread of urogenital pathogens (i.e., Escherichia coli and Hemophilus influenza) from common infectious processes, such as epididymitis and orchitis. 3 Rare pathogens, such as brucella and…”
Section: Discussionmentioning
confidence: 99%